Habitação social em Light Steel Framing como proposta de construção sustentável - Duarte, Daiane Romio (2017)
This research proposes a sustainable social housing at Cuiaba River Valley Metropolitan Area, in Mato Grosso State, Brazil. An existing prototype of a single-family residence containing two bedrooms, integrated living room and kitchen, bathroom, corridor, laundry and balcony is reviewed and improvements are proposed, adding sustainability issues, while maintaining flexibility features and construction techniques in Light Steel Framing as rational construction option. Sustainability analysis are based on Selo Casa Azul criteria. As results, house size is increased to attend accessibility standards, established solar incidence positioning settings, and proposed sealing materials to improve performance and user ́s comfort, becoming a sustainable construction project proposal. It became more adequate to environmental, social, and economic demands, resulting in a higher quality home according to stablished criteria, still maintaining original project benefits. Also, similar prototypes projects in Brazil were compared considering modulation, enlargements possibilities, cross ventilation, and user ́s comfort regarding minimum furniture disposal and people flow.